2005
DOI: 10.1016/j.febslet.2005.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine from vagal stimulation protects cardiomyocytes against ischemia and hypoxia involving additive non‐hypoxic induction of HIF‐1α

Abstract: Electrical stimulation of the vagal efferent nerve improves the survival of myocardial infarcted rats. However, the mechanism for this beneficial effect is unclear. We investigated the effect of acetylcholine (ACh) on hypoxia-inducible factor (HIF)-1a using rat cardiomyocytes under normoxia and hypoxia. ACh posttranslationally regulated HIF-1a and increased its protein level under normoxia. ACh increased Akt phosphorylation, and wortmannin or atropine blocked this effect. Hypoxia-induced caspase-3 activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
102
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 25 publications
11
102
0
Order By: Relevance
“…Specifically, donepezil activated protein expression of VEGF and ChAT, a critical enzyme for de novo ACh synthesis, accelerated endothelial cell proliferation, and inhibited apoptosis, partly independent of cholinergic receptors. These results suggest that donepezil regulates angiogenesis through a non-hypoxic HIF-1 induction pathway, which might be triggered by increased ACh [3,4]. Donepezil was developed to treat patients with Alzheimer's disease as an acetylcholinesterase inhibitor [12,13].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, donepezil activated protein expression of VEGF and ChAT, a critical enzyme for de novo ACh synthesis, accelerated endothelial cell proliferation, and inhibited apoptosis, partly independent of cholinergic receptors. These results suggest that donepezil regulates angiogenesis through a non-hypoxic HIF-1 induction pathway, which might be triggered by increased ACh [3,4]. Donepezil was developed to treat patients with Alzheimer's disease as an acetylcholinesterase inhibitor [12,13].…”
Section: Discussionmentioning
confidence: 95%
“…Our previous study demonstrated that ACh triggers a cell survival signal pathway and transactivates HIF-1 -regulated downstream genes, preventing cells from hypoxia-induced apoptosis [3]. This prompted us to speculate that cholinergic stimuli also possess angiogenesis-promoting effects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, therapeutic strategies focusing on inhibiting myocardial cell apoptosis may be beneficial to impede the occurrence and progression of these cardiovascular diseases. It has been proposed that cardiac myocyte cell loss is the result of apoptosis and is of great importance to various cardiovascular diseases (Gao et al, 2013), and hypoxia is regarded as a key initiator to arouse the loss of cardiac myocyte cells (Kakinuma et al, 2005). Therefore, suppression of hypoxia-induced apoptosis might be beneficial to block the occurrence and progression of many heart diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological action of donepezil is based on an increase in the acetylcholine (ACh) level via inhibition of acetylcholinesterase activity. ACh has been reported to upregulate hypoxia-inducible factor (HIF)-1 alpha even in normoxic conditions [44]. HIF-1 alpha is well known as a master transcriptional factor that positively regulates the expression of glucose metabolism-related genes including GLUTs [45].…”
Section: Discussionmentioning
confidence: 99%